The Process of Reforming of Environmental Aspect with The Sustainable Management for Indonesia’s Environmental Law - Sri Wahyuni (Eduvest - Journal of Universal Studies, 2023)
Access to information and public participation are essential building blocks for sustainable development, preparing citizen to become informed decision markers, offering a basis for stimulating creative solutions to environmental, social and developmental problems, and providing a foundation for building consensus on critical priorities. Governments and institutional governed by transparency, openness, accountability and community participation are more capable of reconciling the needs of present and future generations, of balancing private and public interests, and harmonizing economic development with social and environmental needs. The study aims to find out the process of reforming of environmental aspect with the sustainable management for indonesia’s environmental law. Thus, improved access to information and participation in decision-making will more likely lead to overall sustainable development. All of these developments relate to a more general trend towards promoting “good governance”. All attempts to define the notion of good governance include the elements of transparency, participation, and accountability. Transparency and public participation are the basis for elaborating and working towards more sustainable. Transparency lets the sun shine on actions of governments, and expose protectionism, corruption and other problems arising in conjunction with foreign. Transparency and public participation form the basis for an informed discussion as to how to address challenges relating to the intersection between economic developments on the one hand and social aspects and environmental protection on the other.